An Analysis of Figurative Language in Taylor Swift’s “All Too Well (10 Minute Version)” and Its Pedagogical Implications for English Language Learning - Hesie Diati Safira; Pasca Kalisa (Universitas Islam Negeri Palopo, 2025)
An English song is not only a form of entertainment but also an effective tool for learning languages, especially for students learning English as a foreign language. However, figurative language is often not taught in a practical way in many Indonesian classrooms, making it difficult for students to grasp non-literal expressions. This study applied a qualitative descriptive method by analyzing Taylor Swift’s “All Too Well (10 Minute Version)” using Knickerbocker and Reninger’s (1963) theory. The analysis identified 31 instances of figurative language across nine types, namely hyperbole, irony, metaphor, personification, simile, synecdoche, allusion, metonymy, and paradox, with hyperbole and metaphor appearing most frequently. In addition, perspectives from five students at Universitas Negeri Semarang were gathered through open-ended questionnaires to explore the pedagogical implications of using songs in English learning. The findings showed that students perceived song-based learning as engaging and motivating, reporting improved comprehension of figurative expressions and increased classroom participation. These results indicate that integrating popular songs into English lessons can meaningfully enhance student engagement and foster deeper understanding of figurative language in authentic contexts.